2006
DOI: 10.1074/jbc.m601060200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4-Phosphate Is Required for Translation Initiation in Saccharomyces cerevisiae

Abstract: The small natural product wortmannin inhibits protein synthesis by modulating several phosphatidylinositol (PI) metabolic pathways. A primary target of wortmannin in yeast is the plasma membrane-associated PI 4-kinase (PI4K) Stt4p, which is required for actin cytoskeleton organization. Here we show that wortmannin treatment or inactivation of Stt4p, but not disorganization of the actin cytoskeleton per se, leads to a rapid attenuation of translation initiation. Interestingly, inactivation of Pik1p, a wortmanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 81 publications
4
15
0
Order By: Relevance
“…S3C). These results are in agreement with previous reports that in yeast, latrunculin-B does not result in increased eIF2α phosphorylation and does not affect translation rates (Cameroni et al, 2006;Kandl et al, 2002). Interestingly, however, disassembly of microtubules by nocodazol resulted in a strong phosphorylation of eIF2α in yeast (Fig.…”
Section: Disruption Of F-actin In Mouse Embryonic Fibroblasts Triggersupporting
confidence: 83%
“…S3C). These results are in agreement with previous reports that in yeast, latrunculin-B does not result in increased eIF2α phosphorylation and does not affect translation rates (Cameroni et al, 2006;Kandl et al, 2002). Interestingly, however, disassembly of microtubules by nocodazol resulted in a strong phosphorylation of eIF2α in yeast (Fig.…”
Section: Disruption Of F-actin In Mouse Embryonic Fibroblasts Triggersupporting
confidence: 83%
“…Transcriptional profiles of sec14-1 ts tlg2⌬ mutants indicate TOR signaling is also sensitive to TGN/endosomal function, consistent with growing evidence that central components of the TOR pathway either reside on TGN/endosomal membranes or are otherwise compromised by membrane trafficking defects through that membrane system (Bertram et al, 2000;Chen and Kaiser, 2003;Wedeman et al, 2003;Cameroni et al, 2006;Aronova et al, 2007;Puria et al, 2008;Rohde et al, 2008). Together, these findings define the TGN/ endosomal system as a central hub for control of intracellular homeostatic signaling.…”
Section: Failure Of the Upr And Tor Signaling Pathwayssupporting
confidence: 63%
“…Moreover, we find that combined Sec14/Tlg2 defects evoke dramatic increases in ceramide mass with consequent compromise of the UPR, in part via Sit4 protein phosphatase activity. These data extend studies linking nutrient sensing with membrane traffic through the TGN/endosomal system (Chen and Kaiser, 2003;Cameroni et al, 2006;Yan et al, 2006;Puria et al, 2008;Rohde et al, 2008) and identify ceramide as a quality control reporter for late secretory pathway function.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We recently showed that a decrease of phosphatidyl inositol 4-phosphate (PI4-P) levels on Golgi and ER organelles in a pik1 (PI4-kinase) mutant result in a rapid phosphorylation of eIF2 (Cameroni et al 2006). Like sac1 and drs2 mutants that deregulate the net charge of phospholipids on Golgi/endosomal compartments (see Table 1), the pik1 temperature sensitive mutant is highly sensitive to CPZ at permissive temperature (data not shown).…”
Section: Figmentioning
confidence: 99%